First report of Tomato Brown rugose fruit virus in tomato in Argentina - Obregon, Veronica Gabriela (2023)
Tomato brown rugose fruit virus (ToBRFV) causes severe crop losses worldwide, infecting primarily tomato (Solanum lycopersicum) and pepper (Capsicum annuum). It was detected for the first time in 2014 in Israel (Luria et al., 2017), then in 2015 in Jordan (Salem et al., 2016), and has since spread rapidly to other countries. In the Americas, it was reported in Mexico (Cambrón-Crisantos et al., 2018) and USA (Ling et al., 2019). In December 2022, greenhouse-grown tomato plants from three different growers from Santa Lucía and Lavalle (Corrientes, Argentina) showed similar symptoms to those caused by tobamoviruses. The plants showed mosaic and leaf mottling, narrowing (needle-like) and chlorosis in young leaves. The fruits exhibited necrotic lesions and blotchy ripening (Figures 1-3). More than 50% of the plants in the affected greenhouses showed symptoms, the large incidence being consistent with mechanical transmission of the disease.